2013
DOI: 10.1542/peds.2012-0708
|View full text |Cite
|
Sign up to set email alerts
|

Early Adolescent Music Preferences and Minor Delinquency

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Adolescent music preferences have been linked to problem behavior in cross-sectional studies. Particularly, preferences for loud, rebellious, and so-called "deviant" music predict externalizing problem behavior, such as minor delinquency and substance abuse. WHAT THIS STUDY ADDS:There is a theoretical rationale for associations between music preferences and minor delinquency. Preferences for rock, African American music, and electronic dance music indicate later minor delinquency.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 34 publications
2
36
0
1
Order By: Relevance
“…Even while controlling for these alternative explanations of the development of externalizing behavior, music preference predicted future externalizing behavior. This is in line with the findings of Ter Bogt and colleagues (2013). However, this is in contrast to the study of Steglich et al (2006) who did not find such influence effects from music preference while investigating alcohol use among 129 adolescents of the age of 13 year, using three yearly assessments.…”
Section: Discussionsupporting
confidence: 93%
“…Even while controlling for these alternative explanations of the development of externalizing behavior, music preference predicted future externalizing behavior. This is in line with the findings of Ter Bogt and colleagues (2013). However, this is in contrast to the study of Steglich et al (2006) who did not find such influence effects from music preference while investigating alcohol use among 129 adolescents of the age of 13 year, using three yearly assessments.…”
Section: Discussionsupporting
confidence: 93%
“…Adolescence is a period marked by identity uncertainty and intense pressures to conform (Erikson, 1968;Harter, 1999;Hartup, 1989), and music plays an integral part in helping young people explore their identities and form relationships with peers (Delsing, 2008;ter Bogt, Keijsers, & Meeus, 2013). Indeed, adolescents use music as an identity badge that serves as a symbolic representation of their values and beliefs (Frith, 1981).…”
Section: Why Does Musical Engagement Decline With Age?mentioning
confidence: 99%
“…This suggests a situation similar to that of burnouts in Coleman’s classical work [29]. This idea is further developed by Ter Bogt, Keijsers [30], who argues that music identity has causal effects on behavior based on group closure and social contagion effects. In sum, this strand of theory suggests a causal effect of metal preferences on educational ambitions.…”
Section: Introductionmentioning
confidence: 76%
“…However, in these cases, the child had experienced troubles long before becoming a metal fan [42], leaving metal as an unlikely explanation of the suicide. However, a few recent studies [30, 43] have addressed selection more adequately than the early literature, but still found that metal was related to negative outcomes.…”
Section: Introductionmentioning
confidence: 99%